2015
DOI: 10.18052/www.scipress.com/ilns.42.1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Plant Water Status, Biochemical Attributes and Seed Quality of Black Gram and Green Gram Genotypes under Drought

Abstract: Drought is one of the major abiotic stresses which adversely affect crop growth and production worldwide as water is vital for every aspect of plant growth and development. The present investigation was carried out during the growing seasons (September -December) of 2012 and 2013 to evaluate the response of black gram (Vigna mungo L.) and green gram (Vigna radiata L.) genotypes in terms of some important growth indices, biochemical traits and seed quality under drought stress. Four commonly grown genotypes-T9,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Drought condition was imposed by withholding irrigation 25 days after sowing (Baroowa and Gogoi, 2015;Pooja et al, 2019). Since the experiment was conducted during summer season, there were no unpredicted rains during the entire cropping period hence the drought condition was effectively imposed.…”
Section: Imposing Drought Conditionmentioning
confidence: 99%
“…Drought condition was imposed by withholding irrigation 25 days after sowing (Baroowa and Gogoi, 2015;Pooja et al, 2019). Since the experiment was conducted during summer season, there were no unpredicted rains during the entire cropping period hence the drought condition was effectively imposed.…”
Section: Imposing Drought Conditionmentioning
confidence: 99%
“…In addition, Peng et al( 2006) suggested that anthocyanins may be a beneficial primary antioxidant in rice leaves against oxidative stress induced by environmental stresses. Results of previous studies indicated that drought stress increased proline accumulation (Quilambo, 2004;Baroowa and Gogoi, 2015). Proline has been assigned an important role in adaptation of plants to stress conditions due to its diverse biological effects such as osmotic regulation, antioxidant action, energy transfer as well as carbon and nitrogen source (Kuznetsov and Shevyakova, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Moisture stress at seed filling in lentil significantly reduced above ground biomass, pod number, pod weight, seed number by 41%,71%,71%,77%, respectively (Sehgal et al, 2017). In greengram and blackgram, drought stress leads to reduced leaf number, plant height, shoot and root biomass, leaf area index, leaf water potential, protein content, yield and increased proline, anthocyanin, flavnoids (Baroowa and Gogoi, 2015;Baroowa and Gogoi, 2016).…”
Section: Oil Seedsmentioning
confidence: 99%